Reflexivity in practical theology: reflections from studies of founders' succession in Christian organizations - Bunton, Peter (Practical theology, 2019)
This article explores the issue of reflexivity in practical theology through an analysis of reflexivity's application in three studies of leadership succession from the founders of Christian organizations. After commenting on the issue of reflexivity in qualitative studies in general and specifically in the study of religion, this analysis highlights the use of reflexivity in studying founders' succession at Liberty University, USA, The Church of God in Christ and among American megachurches. This leads to suggestions for how understanding reflexivity in religious studies might be enhanced, by, among other things, consideration of the subject position of researchers in ethnographic ecclesiology compared to other fields of social science and by allowing for theological reflexivity. It is anticipated that this will be useful both for those interested in research methodology and studies in practical theology.